GLOBAL ENVIRONMENTAL REGIME : DI TENGAH PERDEBATAN PAHAM ANTROPOSENTRIS VERSUS EKOSENTRIS - Anna Yulia Hartati (Universitas Wahid Hasyim Semarang, 2012)
Abstract This study describes the global environmental regime in the middle of the struggle between the anthropocentric and ecocentric paradigm. By reason of the fulfillment of human needs-paced dynamic and complex in modern industrial and developmental paradigm, the acts of injustice and arbitrary environmental and natural resource find justification argument. The exploitation of natural resources and the environment as an inevitable consequence of industrialism and developmental paradigms. Earth and environment has lost its existence and rights are essential in terms of ecology and ecosystems. Understand the debate between anthropocentric with ecocentric paradigm. How to manage the environment in order to be able to walk hand in hand with industrialization projects. What is the best solution to bridge both understand the need to apply the material and a deepening understanding of the importance of environmental sustainability continues. This study used a qualitative research method description. Secondary data obtained through the study of the documentary, through magazines, newspapers, books and other resources related to this research topic. Key Word: Environmental regime, anthropocentric, ecocentric.